Teacher Constraints in Implementing the Merdeka Curriculum in Social Studies Learning at MTsN 3 Palu City - Fera Fatmawati; Rus’an Rus’an; Riska Elfira (JURNAL PENDIDIKAN IPS, 2025)
The implementation of the independent curriculum provides teachers with the freedom to design adaptive, contextual, and needs-based learning. However, the reality on the ground indicates that teachers still face various obstacles that directly affect the teaching and learning process. This study was conducted at MTsN 3 in Palu City with the aim of identifying and analyzing the challenges faced by social studies teachers in implementing the independent curriculum. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation. The results of this study indicate that there are three main obstacles faced by teachers: difficulties in developing lesson modules based on learning achievements (CP), challenges in implementing active learning in heterogeneous classrooms, and limitations in facilities and technology proficiency. As a result, the learning process often does not proceed optimally, learning outcomes are not fully achieved, and student motivation declines. Additionally, the lack of training and insufficient teaching materials exacerbate the situation. This research recommends the need for continuous training, the provision of adequate facilities, and collaboration among teachers through working groups as strategic efforts to address the challenges of curriculum implementation. These findings contribute significantly to the development of educational policies that are more responsive to the needs of teachers at the educational unit level. Further research could explore in greater depth the effectiveness of teacher mentoring strategies in the comprehensive and sustainable implementation of the independent curriculum.